Signatures of positive selection apparent in a small sample of human exomes - Tennessen, Jacob A.; Madeoy, Jennifer; Akey, Joshua M. (Genome Research, 2010)
Exome sequences, which comprise all protein-coding regions, are promising data sets for studies of natural selection because they offer unbiased genome-wide estimates of polymorphism while focusing on the portions of the genome that are most likely to be functionally important. We examine genomic patterns of polymorphism within 10 diploid autosomal exomes of European and African descent. Using coalescent simulations, we show how polymorphism, site frequency spectra, and intercontinental divergence in these samples would be influenced by different modes of positive selection. We examine putatively selected loci from four previous genome-wide scans of SNP genotypes and demonstrate that these regions indeed show unusual population genetic patterns in the exome data. Using a series of conservative criteria based on exome polymorphism, we are able to fine-scale map signatures of selection, in many cases pinpointing a single candidate SNP. We also identify and evaluate novel candidate selection genes that show unusual patterns of polymorphism. We sequence a portion of one novel candidate locus, IVL, in 74 individuals from multiple continents and examine global genetic diversity. Thus, we confirm, narrow, and supplement existing catalogs of putative targets of selection, and show that exome data sets, which are likely to soon become common, will be powerful tools for identifying adaptive genetic variation.
10.1101/gr.106161.110